Light Metals 2018 - Martin, Olivier; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The Light Metals symposia at the TMS Annual Meeting & Exhibition present the most recent developments, discoveries, and practices in primary aluminum science and technology. The annual Light Metals volume has become the definitive reference in the field of aluminum production and related light metal technologies. The 2018 collection includes papers from the following symposia: 1.Alumina and Bauxite 2.Aluminum Alloys, Processing, and Characterization 3.Aluminum Reduction Technology 4.Cast Shop Technology 5. Cast Shop Technology: Energy Joint Session 6. Cast Shop Technology: Fundamentals of Aluminum Alloy Solidification Joint Session 7. Cast Shop Technology: Recycling and Sustainability Joint Session 8. Electrode Technology for Aluminum Production 9. Perfluorocarbon Generation and Emissions from Industrial Processes 10. Scandium Extraction and Use in Aluminum Alloys .
Industrial Application of NEUI600 High Efficiency Aluminum Reduction Cell -- RA-550 Cell Technology: UC RUSAL's New Stage of Technology Development -- DX+ Ultra Industrial Version: Preheat Start up and Early Operation -- Selecting Technology for Achieving 300,000 T/Year - Why Do We Need to Compete Pot Technology? -- AP44 Development at Alma -- EGA New D20+ Technology with Reduced Energy Consumption -- Potline Start up without Anode Effect Frequency -- Thermo-electrical Modeling of an Aluminum Reduction Cell -- Restarting Electrochemical Cell with a Cold Metal (D18 Cell) -- Part 4. Cast Shop Technology -- Root Cause Analysis Findings of a Force 3 Explosion -- Condensation Warning System for Dry Material Storage -- A New Aluminium Crucible Skimmer (ACS) for Smelter Plants - Main Benefits Further to Two Years of Experimentation in Industrial Environment -- Drive-in Feeding of Crucibles for Casting Machine -- In-line Salt Fluxing Process with an FFDTM Industrial Experience with a Box-Type Degasser -- The "Alcoa Filter System": A Cost Effective Solution for Enhanced CFF Performance -- Continuous Centrifugal Casting: A Revolutionary Process for Casting Aluminium Tubes -- Development of a Prototype Unit for Continuous Centrifugal Casting of Aluminium Tubes -- Constellium's R&D on the Use of Power Ultrasound in Liquid Aluminum: An Overview -- Molten Metal Cleanliness: Recent Developments to Improve Measurement Reliability -- On-site Benchmark of LiMCA II vs. LiMCA III for Monitor.
Keywords: Metals; Materials -- Analysis; Materials; Metals and Alloys; Characterization and Analytical Technique; Materials Engineering